Extreme climatic events in northern Chile and their impact on the geochemical composition of the Huasco River. (October 2022) - Valdés Durán, Ana; Velásquez, Josefa; Neculqueo, Gloria; Deckart, Katja; Lillo, Dante Cáceres; Frez, Luis Navarro; Tröger, Danny; Quezada, Alejandra Canales; Solé, Marx Buscaglia; Escobar, María Eliana
Abstract: The climatic variations observed in the last 10 years in northern Chile have influenced the dispersion of metals and metalloids accumulated in the transverse valleys. This study is a spatio-temporal geochemical analysis of sediment and water samples from the Huasco River, Chile, obtained during April 2007 and January 2008. There were differences in elemental concentrations along the river between the study years, demonstrating that climate change has affected the study area. These climatic variations were related to ENSO-type cycles: during periods of lower rainfall, enrichment of sediments was observed; in times of greater rainfall, thaws, and water flows, the water samples contained higher elemental concentrations. This pattern is consistent with data obtained in 2015–2016. Elemental provenance analysis indicated that the sediments of the Huasco River were markedly enriched in Ca, Co, Cu, Zn, Cd, Bi, Ag, Pb and La. This enrichment is consistent with the lithology of the study area, which is characterized by the presence of numerous cobalt deposits associated with copper, silver, nickel and cadmium. The results obtained for water samples are consistent with those for sediment samples. We conclude that ionic transfer from sediments to water takes place, caused by chemical dissolution of the minerals that make up the sediments.